2010
DOI: 10.1152/ajprenal.00532.2009
|View full text |Cite
|
Sign up to set email alerts
|

Direct fibrogenic effects of aldosterone on normotensive kidney: an effect modified by 11β-HSD activity

Abstract: Brem AS, Morris DJ, Ge Y, Dworkin L, Tolbert E, Gong R. Direct fibrogenic effects of aldosterone on normotensive kidney: an effect modified by 11␤-HSD activity. Am J Physiol Renal Physiol 298: F1178 -F1187, 2010. First published March 3, 2010 doi:10.1152/ajprenal.00532.2009 can be a profibrotic factor in cardiovascular and renal tissues. This study tests the hypothesis that prolonged Aldo exposure is able to directly induce fibrotic changes in the kidney of a normal nonhypertensive animal. Immortalized rat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Interestingly, many of the studies mentioned above used supra-physiological concentrations of mineralocorticoid coupled with induced injury to achieve these effects. Recently, our laboratory demonstrated that low concentrations of aldosterone (10 nM) can directly induce early fibrotic changes in cultured renal collecting duct cells (CCD) in as little as 48 hours 36 . This response in CCD cells, which contain MR and 11β-HSD-2 is consistent with activation of genomic processes.…”
Section: Recent Advancesmentioning
confidence: 99%
“…Interestingly, many of the studies mentioned above used supra-physiological concentrations of mineralocorticoid coupled with induced injury to achieve these effects. Recently, our laboratory demonstrated that low concentrations of aldosterone (10 nM) can directly induce early fibrotic changes in cultured renal collecting duct cells (CCD) in as little as 48 hours 36 . This response in CCD cells, which contain MR and 11β-HSD-2 is consistent with activation of genomic processes.…”
Section: Recent Advancesmentioning
confidence: 99%
“…We previously reported how aldosterone elicits renal pathologic lesions in the absence of systemic hemodynamic disturbance like hypertension [34]. Here, ecdysone treatment for 2 weeks also caused early mild accumulation of extracellular matrix in renal tubulointerstitium, as revealed by Masson trichrome staining (for collagen) and by peroxidase immunohistochemistry staining for fibronectin (Fig.…”
Section: Ecdysone Confers An Mr Dependent Nephropathic Effectmentioning
confidence: 58%
“…In I/R+Beni+Aldo groups, mice received a continuous infusion of aldosterone by micro pump at a dose of 8 mg kg À1 per day for 4 days. Previous reports [16][17][18][19] and preliminary experiments indicated that this dose of these drugs does not reduce blood pressure in C57BL/6J mice (Supplementary Tables 1 and 2).…”
Section: I/r and Administration Of Drugsmentioning
confidence: 82%